Treatment of large plasma volumes using specific immunoadsorption to desensitize ABO-incompatible kidney-transplant candidates - Lionel Rostaing; Asma Allal; Arnaud del Bello; Federico Sallusto; Laure Esposito; Nicolas Doumerc; Bénédicte Debiol; Audrey Delas; Xavier Game; Nassim Kamar (Journal of Nephropathology, 2016)
Background: ABO-incompatible (ABOi) kidney-transplantation has very good long-term results, i.e. similar to those observed for living-kidney ABO-compatible transplantation. This is because patients are desensitized at pretransplant using apheresis and rituximab therapy, with tacrolimus-based immunosuppression. Objectives: To assess the efficacy of a single, pretransplant (Day –1), specific immunoadsorption session using Glycosorb® columns (anti-A or anti-B; Glycorex Sweden) to treat large volumes of plasma (up to 18 L). Patients and Methods: Prospective single-center study evaluating 12 consecutive patients (6 males), aged 40 (23–59) years. Incompatibilities were A into 0 (8), B into 0 (3), and AB into 0 (1). Pretransplant desensitization relied on rituximab (D–30), tacrolimus, mycophenolic acid, and steroids (all started on D–13), and a single session of specific immunoadsorption on D–1. Immunoadsorption was coupled in tandem with a hemodialysis session. Results: Overall, 15 L (11–18) of plasma were treated per patient, i.e., 0.2 (0.11–0.36 L/kg). Isoagglutinin titers were 1/16 (1/5–1/64) before the procedure, decreasing after 6 hours to 1/5 (1/1–1/16 P = 0.008), and to 1/2 (1/1–1/8; P = 0.05) at completion of the session. The next day, i.e., the day of transplantation, there was no rebound of isoagglutinins [1/4 (1/1–1/5); P = ns]. The procedure was well tolerated with no side-effects and no significant changes in hemoglobin level, platelet counts, fibrinogen, or albumin levels. Conclusions: For ABOi kidney-transplantation, a single, longer, specific immunoadsorption session was very efficient at 1-day pre-transplantation with no rebound. These results should be confirmed when isoagglutinin titers are higher (≥120).